the Impact of Hemodialysis Combined with Hemoperfusion on Metabolism, Cytokines, and Novel Biomarkers in Chronic Kidney Disease Patients: Inflammation, Metabolism, and Biomarkers in CKD - Cai, Ming (Journal of Medical Biochemistry, 2026)
Background: Chronic kidney disease (CKD) often progresses to end-stage renal disease (ESRD), severely affecting patients' lives.Objectives: This article explored the effects of hemodialysis (HD) combined with hemoperfusion (HP) on metabolic indicators, inflammatory cytokines, and novel biomarkers—including oxidative stress markers (malondialdehyde, MDA; superoxide dismutase, SOD), vascular endothelial markers (endothelin-1, ET-1), fibrosis markers (transforming growth factor-beta1, TGF-β1), and metabolic risk markers (homocysteine, Hcy)—in CKD patients.Methods: A retrospective analysis was conducted on clinical data from 72 CKD patients admitted to Changxing County Hospital of Traditional Chinese Medicine from October 2023 to October 2025. Patients were divided into HD+HP group (AG, n=35) and HD group (BG, n=37). Changes in metabolic indicators, inflammatory factors, and novel biomarkers before and after 6 months of treatment were compared.Results: After treatment, the AG showed markedly lower levels of BUN, Scr, iPTH, and β₂-MG compared to the BG (P < 0.05), with a 42.3% reduction in iPTH (326.7 ± 58.4 pg/mL vs. 566.2 ± 89.1 pg/mL). The AG also had markedly lower levels of IL-6, TNF-α, and hs-CRP (P < 0.01). Novel biomarkers including MDA, ET-1, TGF-β1, and Hcy were significantly lower in AG post-treatment (P < 0.05), with SOD activity significantly increased. No visible distinction was noted in adverse event rates (P > 0.05).Conclusion: HD combined with HP can more effectively remove medium and large molecular toxins, improve oxidative stress, endothelial function, and fibrosis markers, and markedly improve calcium-phosphorus metabolism disorders and micro-inflammatory status, providing comprehensive clinical evidence for optimizing blood purification strategies.
Keywords: HD; HP; CKD; metabolism; cytokines; oxidative stress; endothelial dysfunction; fibrosis; homocysteine; biomarkers